Primary spinal tumors and masses in children: a study of 37 cases - Farzan, Abdonaser; Ahmadi, Pooria; Tasdighi, Erfan; Zinatzadeh, Mahmoud Reza; Pourbakhtyaran, Elham (Iranian Journal of Child Neurology, 2022)
Abstract Objectives Spinal cord tumors are a rare diagnosis in children, mostly presented with unspecific symptoms which may pose a problem due to their possible malignancy and further complications. Yet there is little data regarding spinal cord lesions in our country. The aim of this study is to present a series of 37 cases of primary spinal tumors treated at the same institution and briefly review their pathology, symptoms and site of occurrence. Materials & Methods 37 cases of spinal cord tumors and masses were selected from March 2007 to 2017, excluding spinal dysraphism. Data regarding age, sex, clinical presentation, location of the mass, and pathology were retrospectively collected. Results Mean age at diagnosis was 5 years and 8 months (standard deviation: 4.1 years). 21 were male and 16 were female (male-to-female ratio: 1.31). Pathological findings were 9 Neuroepitheliomas (6 Neuroblastoma, 2 Ganglioneuroma, 1 Ganglioneuroblastoma/Ganglioneuroma), 4 Ependymomas, 3 Primitive Neuroectodermal Tumors, 3 Glial tumors, 4 Neurodevelopmental tumors, 3 Lymphomas, 1 Hemangiopericytoma and 1 Neurofibroma. 26 patients had Motor symptoms (74.2%), 14 had pain (40%), 6 showed sensory symptoms (16.6%) and 4 had urinary symptoms (11.4%). The most common location of occurrence was the lumbosacral region. conclusion While differing in pathological composition and location of tumors in comparison to other papers, our study presents possible presentations and/or expected pathologies in pediatric spinal cord tumors.